Richer earnings dynamics, consumption and portfolio choice over the life cycle - Julio Gálvez; Gonzalo Paz Pardo (European Central Bank (ECB), 2023)
Households face earnings risk which is non-normal and varies by age and over the income distribution. We show that allowing for these rich features of earnings dynamics, in the context of a structurally estimated life-cycle portfolio choice model, helps to rationalize the limited participation of households in the stock market and their low holdings of risky assets. Because households are subject to more background risk than previously considered, the estimated model implies a substantially lower coefficient of risk aversion. We also find renewed support for rule-of-thumb investment strategies under the model with the nonlinear earnings process.
Keywords: G11; G12; D14; D91; J24; H06; 330; stock ownership; earnings risk; wealth accumulation; household finance; simulated method of moments